1997
DOI: 10.1111/j.1600-0536.1997.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis from pyoctanin

Abstract: Although pyoctanin is widely used in medicine, there are hardly any reports of contact allergy to it. Most reports of side-effects refer to irritant reactions after topical application. We describe 2 patients who developed pyoctanin contact dermatitis after long-term application on damaged skin. Positive patch test results down to concentrations of 0.0025% and 0.05% aqueous pyoctanin solution, respectively, were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is also used in agriculture as a soil fungicide, plant bactericide, and acaricide (Fiege et al, 2000). Studies have shown that some patients tested with a concentration range of 0.3% to 6% transdermal patches (7-147 µM) were allergic to this substance (Schoppelrey et al, 1997). At a high concentration (200 µM), hexachlorophene dramatically increased the IL-1α secretion in the RhE and FTS models ( Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…It is also used in agriculture as a soil fungicide, plant bactericide, and acaricide (Fiege et al, 2000). Studies have shown that some patients tested with a concentration range of 0.3% to 6% transdermal patches (7-147 µM) were allergic to this substance (Schoppelrey et al, 1997). At a high concentration (200 µM), hexachlorophene dramatically increased the IL-1α secretion in the RhE and FTS models ( Figure 4A).…”
Section: Discussionmentioning
confidence: 99%